A surface modification layer with cobalt aluminate inhibits 4.6 V high-voltage phase transition of LiCoO2. (1st October 2022) - Li, Zhi-Wei; Jiang, Yun-Shan; Xia, Yang; Deng, Liang; Sun, Mei-Yan; Shao, Guang-Jie; Zhao, Lei; Yu, Fu-Da; Wang, Zhen-Bo
Highlights: We utilized a simple and feasible modification strategy by using a surface modification layer with cobalt aluminate to achieve ultra-long cyclicity of LiCoO2 at 4.6 V. This strategy can prevent direct contact between the electrode and electrolyte without hindering the passage of lithium ions, and reduce the loss of active cobalt. It is found that Co (II) of the modified layer is oxidized Co (III) in the redox reaction, which provides extra electrons to induce the deintercalation/intercalation of lithium ions for the half-cell in process of the initial charge/discharge, which might be the first reported in the cathode at high-voltage conditions. As revealed by in-situ XRD, the surface modification layer with cobalt aluminate inhibits phase transitions from O3 to H1–3 phase at a charge voltage of approximately 4.55V. The surface modification of LCO exhibits excellent electrochemical performance, delivering a high initial capacity (215 mAh g −1 ), superior rate capability (131 mAh g −1 at 5C) and long cycling life (80.6%@500 cycles) in half-cells, which is much superior to other reported works. Abstract: Inhibiting the high-voltage phase transition of lithium cobaltate has been a major challenge. Here, we utilize a simple and feasible strategy by using the surface modification layer with cobalt aluminate to achieve ultra-long cyclicity of LiCoO2 at high voltage. This strategy can protect the electrode from electrolyte attack without hindering the migration of lithium ions, and reduce the loss of active cobalt. Simultaneously, Co (II) of the modified layer is oxidized Co (III) in the redox reaction, which provides extra electrons to induce the deintercalation/intercalation of lithium ions for the half-cell in process of the initial charge/discharge. Electrochemical in-situ characterization reveals that the compound material presents excellent high-voltage structural stability due to reversible phase transition induced by the surface modification layer. As a result, CoAl2 O4 coated LiCoO2 achieves excellent ultra-long cycling with high-capacity retention of 86.3% after 500 cycles at 1 C (1C = 274 mA g −1, 3.0–4.6 V). Graphical abstract: The surface modification layer with cobalt aluminate is introduced to overcome the phase transitions and efficiently improve the electrochemical performance. Image, graphical abstract